Ekstraksi, Karakterisasi dan Aktivitas Antioksidan Hyaluronan dari Vitereous Humor Mata Tuna Sirip Kuning (Thunnus albacares) - Wini Trilaksani; Bambang Riyanto; Tri Wahyuningsih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Vitreous humor is a part of the tuna fish eye that plays a role in maintaining the brightness of the eye and contains hyalocytes having function to produce hyaluronan. Hyaluronan is thought as an antioxidant to prevent unsaturated fatty acids damage in tuna fish eye caused by free radicals. Hyaluronan from vitreous humor tuna fish eye has not been widely studied. This study was aimed to extract the hyaluronan found in vitreous humor of tuna fish eye and determine its characteristics. Extraction of hyaluronan consisted of presipitation, centrifugation, enzyme digestion, defatting, dialysis, and freeze drying. Antioxidant activity was determined by three methods comprising 1,1-diphenyl-2-picrylhydrazyl2,2-azinobis (DPPH), 3-ethylbenzo-thiozoline-6-sulfonic acid (ABTS), and ferric reducing antioxidant power (FRAP). Vitreous humor tuna fish eye had a proportion of 31% of eye, pH value 6.905±0.0083, viscosity 195.56±12.86 cP, water 98.09±0.49%, and glutamic acid 932.06±3.80 mg/L. The hyaluronan yield was about 0.005±0.001%. The IC50 antioxidant activity of hyaluronan against DPPH was 25.52±0.22 mg/mL while the inhibition capacity on ABTS was 1.92±0.08% and the ferric reduction capacity was 9.34±0.55 µM/g. These results indicates that the antioxidant activity of hyaluronan from vitreous humor tuna fish eye is low.